Trends in the sources and sinks of carbon dioxide - Le Quéré, Corinne; Raupach, Michael R.; Canadell, Josep G.; Marland, Gregg; Bopp, Laurent; Ciais, Philippe; Conway, Thomas J.; Doney, Scott C.; Feely, Richard A.; Foster, Pru; Friedlingstein, Pierre; Gurney, Kevin; et al. (Nature geoscience, 2009)
Efforts to control climate change require the stabilization of atmospheric carbon dioxide concentrations. An assessment of the trends in sources and sinks of atmospheric carbon dioxide suggests that the sinks are not keeping up with the increase in carbon dioxide emissions, but uncertainties are still large. Efforts to control climate change require the stabilization of atmospheric CO 2 concentrations. This can only be achieved through a drastic reduction of global CO 2 emissions. Yet fossil fuel emissions increased by 29% between 2000 and 2008, in conjunction with increased contributions from emerging economies, from the production and international trade of goods and services, and from the use of coal as a fuel source. In contrast, emissions from land-use changes were nearly constant. Between 1959 and 2008, 43% of each year's CO 2 emissions remained in the atmosphere on average; the rest was absorbed by carbon sinks on land and in the oceans. In the past 50 years, the fraction of CO 2 emissions that remains in the atmosphere each year has likely increased, from about 40% to 45%, and models suggest that this trend was caused by a decrease in the uptake of CO 2 by the carbon sinks in response to climate change and variability. Changes in the CO 2 sinks are highly uncertain, but they could have a significant influence on future atmospheric CO 2 levels. It is therefore crucial to reduce the uncertainties.